Demographic Administration Service Utilizing the Electronic Service Application Information System (SIAPEL) - Ihsan; Hayat; Didik Supriyanto (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Abstract. This research examines how demographic administration services are carried out through the SIAPEL application at the Population and Civil Registry Office of Malang City, as well as the key challenges that arise during its use. The study applies a qualitative approach and follows the Miles and Huberman analysis model, which includes data collection, reduction, presentation, and conclusion verification. Findings show that SIAPEL has successfully reduced bureaucratic steps that were previously slow and complicated, making public service more practical and predictable for residents. Even so, several issues still appear, such as limited user participation, uneven readiness of supporting facilities, and gaps in officer competencies, which affect service consistency and user experience. On the other hand, the commitment of implementing staff plays a major role in keeping the system running and helping residents adapt to the digital process. The study suggests that better infrastructure support, improved officer skills, and stronger system integration across government units are needed to maximize the potential of SIAPEL as a sustainable digital service platform.